TGF‐β activates pericytes via induction of the epithelial‐to‐mesenchymal transition protein SLUG in glioblastoma. (5th May 2021) - Wirsik, Naita M.; Ehlers, Jakob; Mäder, Lisa; Ilina, Elena I.; Blank, Anna‐Eva; Grote, Anne; Feuerhake, Friedrich; Baumgarten, Peter; Devraj, Kavi; Harter, Patrick N.; Mittelbronn, Michel; Naumann, Ulrike
Abstract: Aims: In primary central nervous system tumours, epithelial‐to‐mesenchymal transition (EMT) gene expression is associated with increased malignancy. However, it has also been shown that EMT factors in gliomas are almost exclusively expressed by glioma vessel‐associated pericytes (GA‐Peris). In this study, we aimed to identify the mechanism of EMT in GA‐Peris and its impact on angiogenic processes. Methods: In glioma patients, vascular density and the expression of the pericytic markers platelet derived growth factor receptor (PDGFR)‐β and smooth muscle actin (αSMA) were examined in relation to the expression of the EMT transcription factor SLUG and were correlated with survival of patients with glioblastoma (GBM). Functional mechanisms of SLUG regulation and the effects on primary human brain vascular pericytes (HBVP) were studied in vitro by measuring proliferation, cell motility and growth characteristics. Results: The number of PDGFR‐β‐ and αSMA‐positive pericytes did not change with increased malignancy nor showed an association with the survival of GBM patients. However, SLUG‐expressing pericytes displayed considerable morphological changes in GBM‐associated vessels, and TGF‐β induced SLUG upregulation led to enhanced proliferation, motility and altered growth patterns in HBVP. Downregulation of SLUG or addition of a TGF‐β antagonising antibody abolished these effects. Conclusions: We provide evidence that in GA‐Peris, elevated SLUG expression is mediated by TGF‐β, a cytokine secreted by most glioma cells, indicating that the latter actively modulate neovascularisation not only by modulating endothelial cells, but also by influencing pericytes. This process might be responsible for the formation of an unstructured tumour vasculature as well as for the breakdown of the blood–brain barrier in GBM. Abstract : In GBM‐vessel‐associated pericytes elevated SLUG expression, paralleled by the induction of cell proliferation, mitochondrial activity and cell migration, is induced by TGF‐β, a cytokine highly expressed by glioma cells. This indicates that GBM cells actively modulate neovascularization not only by modulating endothelial cells, but also by influencing the function and characteristics of adjacent vessel‐associated pericytes. This process might be responsible for the formation of an unstructured tumor vasculature as well as for the breakdown of the BBB in the tumor area.